Cortical Thymocytes Along With Their Selecting Ligands Are Required for the Further Thymic Maturation of NKT Cells in Mice - Klibi, Jihene; Benlagha, Kamel (Frontiers in Immunology, 2020)
Following positive selection, NKT cell precursors enter an “NK-like” program and progress from an NK- to an NK+ maturational stage to give rise to NKT1 cells. Maturation takes place in the thymus or after emigration of NK- iNKT cells to the periphery. In this study, we followed the fate of injected iNKT cells at the NK- stage of their development in the thymus of a series of mice with differential CD1d expression. Our results indicate that CD1d-expressing cortical thymocytes, and not epithelial cells, macrophages, or dendritic cells, are necessary and sufficient to promote the maturation of thymic NKT1 cells. Migration out of the thymus of NK- iNKT cells occurred in the absence of CD1d expression, however CD1d expression is required for maturation in peripheral organs. We also found that the natural ligand iGb3 (Isoglobotriosylceramide), and the cysteine protease Cathepsin L, both localizing with CD1d in the endosomal compartment and crucial for NKT cell positive selection, are also required for NK- to NK+ NKT cell transition. Overall, our study indicates that the maturational transition of NKT cells require continuous TCR/CD1d interactions and suggest that these interactions occur in the thymic cortex where DP cortical thymocytes are located. We thus concluded that key components necessary for positive selection of iNKT cells are also required for subsequent maturation.